Do you know the labour ward sister? - Editorial Office (Curationis, 1980)
Who is the Labour Ward Sister? Perhaps she deserves above all the title “Midwife Specialist” — continually up-to-date in her knowledge of obstetrics, the “diagnostician” and colleague of the obstetrician; one cannot function adequately without the other.